KEMAMPUAN PERTUMBUHAN PERUSAHAAN MEMODERASI PENGARUH FINANCIAL DISTRESS TERHADAP AUDITOR SWITCHING - Pradana Pinto, Timtom Bagus; Gayatri, . (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The purpose of this research is to find empirical evidence about the ability of the company's growth moderating influence on the company's financial distress switching auditors in Indonesia. The data used is data manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2011-2014. Variables used in this research is the growth of the company (X1), financial distress (X2) and auditor switching (Y). The study was conducted using Logistic Regression (Logistic Regression). The results showed that the positive effect on the financial distress switching auditors. Growth companies able to moderate influence on the auditor's financial distress switching.
Keywords: Auditor Switching, Rotation Auditor, Audit Tenure, Independence, Financial Distress, Company Growth